Granulocyte transfusions collected after steroid priming for severe infections during neutropenia: A single center experience - Vráblová, Lucia; Blahutová, Šárka; Čermáková, Zuzana; Raida, Luděk; Szotkowski, Tomáš; Hubáček, Jaromír; Rohoň, Peter; Urbanová, Renata; Indrák, Karel; Papajík, Tomáš; Kolář, Milan; Faber, Edgar (Transfusion clinique et biologique, 2019)
BACKGROUND: There is no universally accepted opinion on the use of granulocyte transfusions collected using apheresis (GTA) in neutropenic patients and severe infection. PATIENTS AND METHODS: The efficacy and safety of GTAs transfused at a single center over 10 years were analyzed retrospectively. GTAs were harvested from voluntary unrelated donors after priming with methylprednisolone using continuous apheresis and hydroxyethylstarch as sedimentation agent. RESULTS: 41 patients with neutropenia and hematologic malignancy (15 females and 26 males aged 22-69 (median 45.5)) were given a median 3.5 GTAs per patient (range: 1-17) containing a median 1.39×1010 granulocyte/GTA (range: 0.65-2.81). The indications for GTA use were soft tissue inflammation, sepsis, and pneumonia in 30, 22, and 14 cases, respectively. After GTA complete (30 patients: 73.2%) or partial (6 patients: 14.6%) healing of the infection was achieved. The success rate was 91.7% in soft tissue infections, 66.7% in invasive fungal infections, and 68% in sepsis. Septic shock (documented in 12 cases) was associated with a poor response (P<0.03; Chi-square test). Clinical worsening was observed in six cases (14.6%); four patients died. No significant short-term side effects of GTA treatment were recorded. CONCLUSIONS: In our study GTAs collected after steroid priming and used for the treatment of infection during severe neutropenia have shown comparable efficacy with several previously reported trials. However retrospective fashion of our study and inhomogeneous group of patients do not allow any firm conclusions. Prospective studies (including patients' registries) are needed for the better clarification of the role and the dose of GTAs necessary for the successful infection management during neutropenia.
Keywords: senioři; Febrile Neutropenia; febrilní neutropenie; Soft Tissue Infections; pneumonie; methylprednisolon; infekce měkkých tkání; Sepsis; Pneumonia; antiinfekční látky; hematologické nádory; Retrospective Studies; Methylprednisolone; deriváty hydroxyethylového škrobu; Prolonged severe neutropenia; Anti-Infective Agents; Hematologic Neoplasms; Middle Aged; mužské pohlaví; Granulocytes; Blood Component Removal; Adult; mladý dospělý; granulocyty; Blood Component Transfusion; Hydroxyethyl Starch Derivatives; Hematopoietic Stem Cell Transplantation; Young Adult; ženské pohlaví; mykózy; transplantace hematopoetických kmenových buněk; retrospektivní studie; Humans; separace krevních složek; Severe infection; Mycoses; sepse; lidé středního věku; dospělí; Neutropénie sévère prolongée; Granulocytes de l’aphérèse; Infection sévère; Female; Aged; Granulocyte from apheresis; lidé; Male; převod jednotlivých krevních složek